2021
DOI: 10.3390/nu13041280
|View full text |Cite
|
Sign up to set email alerts
|

Single High-Dose Vitamin D Supplementation as an Approach for Reducing Ultramarathon-Induced Inflammation: A Double-Blind Randomized Controlled Trial

Abstract: Purpose: A growing number of studies indicate the importance of vitamin D supplementation for sports performance. However, the effects of a single high-dose vitamin D supplementation on ultramarathon-induced inflammation have not been investigated. We here analyzed the effect of a single high-dose vitamin D supplementation on the inflammatory marker levels in ultramarathon runners after an ultramarathon run (maximal run 240 km). Methods: In the study, 35 runners (amateurs) were assigned into two groups: single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…High intensity exercises lead to transient muscle fibre damage, performance deterioration, increased inflammation processes [1] and oxidative stress induced by the generation of free radicals [2]. All those factors are associated with muscle injury, and occur during normal competition, especially when the duration or intensity of sport competition is very high.…”
Section: Introductionmentioning
confidence: 99%
“…High intensity exercises lead to transient muscle fibre damage, performance deterioration, increased inflammation processes [1] and oxidative stress induced by the generation of free radicals [2]. All those factors are associated with muscle injury, and occur during normal competition, especially when the duration or intensity of sport competition is very high.…”
Section: Introductionmentioning
confidence: 99%
“…The following procedures were adapted from our previous study [ 53 ]. Blood (9 mL) was collected five times: immediately before, immediately after, 2 h, 6 h, and 24 h after every test.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that vitamin D supplementation reduces ultramarathon-induced inflammation [ 14 ]. The anti-inflammatory activity of vitamin D is well recognized, as its active form has been shown to repress the expression of proinflammatory cytokines [ 14 ].…”
Section: Introductionmentioning
confidence: 99%